Dokumen kontrak : inspection, servicing, preventive and breakdown maintenance of fire protection installation and auxiliary equipment at Universiti Teknologi Malaysia Skudai Johor - Universiti Teknologi Malaysia; Syarikat Azcon (Skudai : Universiti Teknologi Malaysia, 2000)
03